Single Switch DC-DC Converter for Battery Feed Electrical Vehicle - S, Kalpana.; B, Mohamed Ismail.; R, Riveka.; M, Shagar Banu. (Research Parks Publishing LLC, 2023)
A new single-switch transformer less lift DC-DC converter has been suggested that energy component cars could benefit from a new single-switch transformer reduced lift DC-DC converter. The newly developed topology makes use of a different capacitor multiplier and an integrated LC2D yield organise in order to improve the voltage addition of the converter and reduce the voltage load that is placed on the force switch. In addition, the suggested converter features a broad voltage gain range, which allows it to accommodate a broad variety of voltage swings produced by the energy component. The operating standards of the suggested converter as well as its consistent state examinations are presented below. Recreation was utilised in the production of a scaled-down, exploratory model that had 800 V and 1 kW. The outcomes of the re-enactment demonstrate that the framework is sufficient.